Tanggo-Tanggo: An Ethnobiological Study of a Traditional Batak Toba Food for Biodiversity Learning through Educational Videos - Daniel Shilkia M.; Fajar Adinugraha; Sunarto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Traditional foods are part of indigenous knowledge or local wisdom that reflects cultural identity, natural potential, and the social values of local communities. However, knowledge related to traditional foods is often transmitted orally from generation to generation and has not been well documented scientifically, particularly regarding the use of local biodiversity. Tanggo-tanggo is a traditional Batak food that represents the close relationship between culture and local biodiversity. This study aims to examine Tanggo-tanggo from an ethnobiological perspective and develop local culture-based learning media for formal education in schools, integrating it with community-based informal learning to support cultural conservation. The research was conducted using an ethnobiological approach, and data were collected through interviews with seven informants using snowball sampling and participatory observation. The process of making Tanggo-tanggo involves 16 species, comprising 15 plant species and 1 animal species, namely pigs (Sus scrofa domesticus), with plant parts used including rhizomes, fruits, flowers, tubers, and leaves. The processing techniques are simple and have been passed down from generation to generation as part of Batak community traditions. The results show that Tanggo-tanggo not only functions as a dish but also as an expression of cultural identity and rich local knowledge. This research is expected to contribute to ethnobiological documentation, support local culture-based education, and promote food security, natural resource conservation, and community empowerment.